Evaluasi Training Basic Aircraft Maintenance Electrical Avionic Menggunakan Metode Kirkpatrick pada PT X - Alissa Khairunnisa; Rosento Rosento (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
To compete in the global MRO (Maintenance, Repair & Overhaul) industry, qualified human resources are required. Therefore, a training program is conducted for employees to ensure goals are met, particularly in the field of aircraft maintenance. This program aims to evaluate using the Kirkpatrick Four-Level method, which identifies Level 1 (reaction), Level 2 (learning), Level 3 (behavior), and Level 4 (results). The study aims to assess and analyze the efficiency and effectiveness of the training, its impact on performance, such as productivity improvement, service quality, cost reduction, and measure the participants' understanding and behavior changes. In addition, the Return on Training Investment (ROTI) achieved by PT X is also analyzed. This study uses a non-statistical quantitative approach, focusing on data management to assess the company's progress based on annual training reports. The research results indicate that at Level 1, the overall average reached 4.09 across 4 parameters. At Level 2, the participants' average pre-test score was 78.5, and the post-test score was 87.8. At Level 3, discipline improved with a total score of 94.5 and an average of 4. At Level 4, ROTI reached 130.22%, with a return on investment of 99,550.97 from a training cost of 76,449.03.